Yeasts as microbial cell factories for sustainable production of biofuels. (June 2021) - Liu, Zihe; Moradi, Hamideh; Shi, Shuobo; Darvishi, Farshad
Abstract: Sustainable production of biofuels has provided an attractive alternative to fossil fuels, which has relieved the concern regarding energy supply and global climate change. Currently, interest in metabolic engineering of yeasts as microbial cell factories for biofuel production, which varies from short-chain ethanol to long-chain fatty acid-derived molecules, is growing. The commercial production of new energy-dense biofuels using yeasts and new synthetic biology tools is now possible due to recent developments in metabolic engineering. Here, it is attempted to comprehensively and critically review the latest advances in metabolism-targeted strategies and the production of different types of biofuels using yeasts. Furthermore, the key challenges and perspectives have been discussed for improving yeast biorefineries for the production of biofuels, such as host compatibility of heterologous genes, substrate extension for alternative feedstocks, better tools for reprogramming cell metabolism, host robustness for tolerating or alleviating toxicity induced by end products, and new design principles with predictable behaviors for the constructed biological systems. Highlights: Recent advances in biofuel production by engineered yeasts were reviewed in detail. New and synthetic pathways in yeasts were illustrated for various biofuels. Bottlenecks and barriers in sustainable biofuel production by yeasts were addressed. Future research trends were clarified to access sustainable biofuel by yeasts.